PEMIKIRAN POLITIK RECEP TAYYIB ERDOGAN DAN PERKEMBANGANNYA DI TURKI - Savri Yansah (Manthiq, 2018)
The background of this research is the secular state, initiated by Mustafa Kemal Ataturk in developing secular ideol- ogy in Turkey. On March 3, 1924 He formally abolished the Caliph on the earth of Turkey. For Mustafa Kemal Atattur, the inter- ference of Islam in various political activities, has brought decline of Islam. Mustafa Kemal promoted secular ideology to creat a new civilization. Therefore, if Turkey advanced and modern, he must leave religion. This study used qualitative approadch with library research method. With the formulation of this problem, namely: how political thoughts Recep Tayyib Erdogan and its development in Turkey and its contribution to Turkish politics. Based on the finding of this study, it can be ancluded that the Recep Tayyip Erdogan‟s thought succeded to change Turkey in to healthy and groving country. With his politeness and skill in politics, Recep Tayyib Erdogan through his political thought, assured the Turkish people that the secularism that had rooted in the time of Mustafa Kemal Attaturk, who abolished Islamic values, Recep Tayyib Erdogan also assured his people that with the Islamic identity, the glory of the Ottoman Empire, an Empire not only strong in defense, but also in the economy as well as making Islam a solution in life (Al-Islam huwa Al-Hall). The contribution of Recep Tayyib Erdogan‟s political thought a) is able to apply Islamic values in the life of the nation b) Islamic concepts combined in politics for the welfare of his people in the Turkish political order and c) and also is able to contribute in creating peace.